The Immunology of Wild Rodents: Current Status and Future Prospects - Viney, Mark; Riley, Eleanor M. (Frontiers in Immunology, 2017)
Wild animals’ immune responses contribute to their evolutionary fitness. These responses are moulded by selection to be appropriate to the actual antigenic environment in which the animals live, but without imposing an excessive energetic demand which compromises other component of fitness. But, exactly what these responses are, and how they compare with those of laboratory animals, has been little studied. Here, we review the very small number of published studies of immune responses of wild rodents, finding general agreement that their humoral (antibody) responses are highly elevated when compared with those of laboratory animals, and that wild rodents’ cellular immune system reveals extensive antigenic exposure. In contrast, proliferative and cytokine responses of ex vivo-stimulated immune cells of wild rodents are typically depressed compared with those of laboratory animals. Collectively, these responses are appropriate to wild animals’ lives, because the elevated responses reflect the cumulative exposure to infection, while the depressed proliferative and cytokine responses are indicative of effective immune homeostasis that minimizes immunopathology. A more comprehensive understanding of the immune ecology of wild animals requires (i) understanding the antigenic load to which wild animals are exposed, and identification of any key antigens that mould the immune repertoire, (ii) identifying immunoregulatory processes of wild animals and the events that induce them, and (iii) understanding the actual resource state of wild animals, and the immunological consequences that flow from this. Together, by extending studies of wild rodents, particularly addressing these questions (while drawing on our immunological understanding of laboratory animals), we will be better able to understand how rodents’ immune responses contribute to their fitness in the wild.